Mitochondrial dysfunction in Wilson disease: a systematic review and meta–analysis across human and animal models - Amin, Raya; Medici, Valentina; Fausak, Erik D.; Sierra, Keren; Li, Ieleen; Gong, Joshua; Giulivi, Cecilia (Frontiers in Molecular Biosciences, 2025)
Background & AimsWilson disease (WD) is a genetic disorder of copper metabolism caused by ATP7B mutations, leading to hepatic and systemic copper accumulation. While lysosomes are early storage sites, mitochondria appear highly vulnerable to copper toxicity. We performed a systematic review and meta–analysis to assess mitochondrial outcomes in WD patients and animal models.MethodsPubMed, Scopus, and SciFinder were searched through 11 September 2025, for studies reporting hepatic mitochondrial endpoints in WD (in patients and models using mice, rats, and dogs). Outcomes included mitochondrial copper, morphology, oxidative stress, mtDNA copy number, ATP production, and respiratory Complex activities. Random–effects meta–analyses were conducted.ResultsThirteen studies met the inclusion criteria. Mitochondrial copper was consistently elevated (standardized mean difference ±standard error: 6.7 ± 0.9, P < 0.001), with ultrastructural abnormalities (4 ± 2, P = 0.012). Oxidative stress markers increased (2.9 ± 0.9, P = 0.001), while MnSOD and aconitase declined with disease progression. mtDNA copy number was reduced (−0.7 ± 0.3, P = 0.032). ATP synthesis (−1.5 ± 0.6, P = 0.023) and Complex activities (−1.0 ± 0.3, P = 0.001) were impaired, especially in older or symptomatic subjects. Citrate synthase activity increased (2.8 ± 0.9, P = 0.003), consistent with compensatory biogenesis. Several abnormalities appeared in presymptomatic or young animals.ConclusionAcross human and animal studies, hepatic mitochondria in WD exhibit copper accumulation, structural injury, impaired bioenergetics, oxidative stress, and mitochondrial genome loss. Mitochondrial dysfunction arises early and worsens with progression, highlighting it as a central pathogenic feature and therapeutic target.